Hollow Carbon Spheres with Abundant Micropores for Enhanced CO2 Adsorption - Li, X.; Bai, S.; Zhu, Z.; Sun, J.; Jin, X.; Wu, X.; Liu, Jian (American Chemical Society, 2017)
The interest in the design and controllable fabrication of hollow carbon spheres (HCSs) emanates from their tremendous potential applications in adsorption, energy conversion and storage, and catalysis. However, the effective synthesis of uniform HCSs with high surface area and abundant micropores remains a challenge. In this work, HCSs with tunable microporous shells were rationally synthesized via the hard-template method using resorcinol (R) and formaldehyde (F) as a carbon precursor. HCSs with a very high surface area (1369 m2/g) and abundant micropores (0.53 cm3/g) can be obtained with the assistance of additional inorganic silanes (TEOS) simultaneously with the carbon source (RF). Interestingly, the extra-abundant micropores showed favorable adsorption for CO2, resulting in a 1.5 times increase in the CO2 adsorption capacity compared to that of normal HCSs under the same conditions. Meanwhile, these HCSs hold potential for use in the separation of gases such as CO2 and N2. © 2017 American Chemical Society.